Dosa Pikiran dan Integritas Perkawinan: Analisis Matius 5:27-28 dalam Perspektif Eksegetis - James Lola; Berniwati Berniwati; Jinersita Tappi; Yuelianto Salem (JURNAL LUXNOS, 2026)
One of the main causes of divorce in Christian marriages is adultery. Adultery itself is understood as sexual intercourse between a person and someone other than their husband or wife. However, in Matthew 5:27-28, Jesus, in the Sermon on the Mount, explains that the prohibition against adultery is not limited to sexual intercourse alone; rather, whoever looks at a woman with lust has already committed adultery in his heart. Jesus’ statement raises difficulties in understanding what is meant by committing adultery in one’s heart, and whether adultery in the heart can be used as grounds for divorce. This study, using the historical-grammatical method, will seek to determine the meaning of Jesus’ words in Matthew 5:27–28 and whether this “adultery in the heart” can lead to divorce. This study is motivated by the tendency to understand adultery solely as the physical act of sexual intercourse between a person and someone who is not their lawful spouse. However, in Matthew 5:27–28, Jesus emphasizes that adultery does not occur only through outward actions but can also arise through deliberate sexual desire within the heart. The results of the study indicate that Jesus’ statement in this text is part of the Sermon on the Mount, specifically a series of antitheses that affirm a truth transcending the legal-formal interpretations of the scribes and Pharisees. In this context, Jesus did not abolish the Law, but rather deepened its meaning by highlighting the root of sin that lies in the human heart and mind. Adultery in the heart is an act of sexual fantasy that can be classified as a psychosexual disorder and can cause damage to a marriage and even lead to divorce.